Strength training for endurance cyclists - Rønnestad, B. R. (Concurrent aerobic and strength training. Scientific basics and practical applications, 2019)
Amongst well-trained cyclists, there is a small difference in performance. Therefore, coaches and athletes strive for the optimal training strategies. As a consequence of this, strength training off the bike, as a mean of optimizing the performance on the bike, has received gradually more attention during the last decade. Particularly, the effects of adding heavy strength training to the normal endurance training on the bike have been a topic of increasing interest amongst both the scientists and the practitioners. The purpose of this chapter is to briefly describe how strength training influences important physiological determinants of cycling endurance performance, present potential mechanisms behind the effects of strength training on cycling performance, and give practical recommendations for combination of strength- and endurance training. Abstract from author